219k views
18 votes
If

f(x) = 2x3 + 6, which function satisfies
(fof-1) (x) = x and
(f-10 f)(x) = x? (1 point)

User Retro
by
6.0k points

1 Answer

8 votes

Answer:

Both are true.

Explanation:

If f(x) = 2x³ + 6

To find the inverse of the given function,

Rewrite the function in the form of an equation,

y = 2x³ + 6

Interchange the variables x and y,

x = 2y³ + 6

Solve for y,

2y³ = x - 6

y =
\sqrt[3]{((x-6))/(2)}

Rewrite the equation in the form of a function,


f^(-1)(x)={\sqrt[3]{((x-6))/(2)}


(fof^(-1))(x)=f[f^(-1)(x)]

=
2(\sqrt[3]{((x-6))/(2)})^3+6

= (x - 6) + 6

= x


(f^(-1)of)(x)=f^(-1)[{f(x)]


={\sqrt[3]{((2x^3+6-6))/(2)}


={\sqrt[3]{((2x^3))/(2)}

= x

Therefore, both the statements are true.

User SourceC
by
5.1k points